A Rare Case of Lateral Canthal Gouty Tophus Presenting as an Eyelid Mass - Austin S. Nakatsuka; Timothy F. McDevitt; Pamela S. Tauchi-Nishi (Case Reports in Ophthalmological Medicine)
A 41-year-old man with a history of gout presented with an enlarging eyelid growth. Clinical examination revealed a mildly indurated nodule at the lateral canthus. Following resection, histopathological examination revealed needle-shaped, crystalline material surrounded by multinucleated giant cells, findings consistent with gouty tophus. This represents just the sixth case of gouty tophus of the eyelid reported in the literature.